Effect of activated carbon on organic acids in peach pulp - Arslanoglu, FN; Kar, F; Arslan, N (Springer India, 2005)
The effect of activated carbon (AC) usage on lactic acid, malic acid and citric acid in peach pulp was examined at carbon concentrations of 0.5, 1, 3, 5 kg AC/m(3) peach pulp and the temperature range of 20-50 degrees C. The adsorption (%) increased with increasing AC concentration and contact time. Five kinetic models were evaluated to fit the experimental data for lactic acid which included the pseudo-first order, the pseudo-second order, the modified Freundlich, the pore diffusion and the Elovich equations. The kinetic parameters of each model were calculated. It was found that the adsorption process could be well described with the Elovich model for adsorption kinetic, The activation energies for adsorption of lactic acid from peach pulp by powdered and granular AC were 5.14 and 9,29 kJ/mol. respectively. This low activation energy value showed that the adsorption process was diffusion controlled. Adsorption (14) of lactic acid increased with increasing the AC concentration and contact time. Bill the AC concentration and contact little did not cause a regular change in the adsorption (%) of malic and citric acids.
Keywords: peach pulp; activated carbon; adsorption; organic acids